2017
DOI: 10.2147/ijn.s130608
|View full text |Cite
|
Sign up to set email alerts
|

Lipase degradation of plasticized polyvinyl chloride endotracheal tube surfaces to create nanoscale features

Abstract: Polyvinyl chloride (PVC) endotracheal tubes (ETTs) nanoetched with a fungal lipase have been shown to reduce bacterial growth and biofilm formation and could be an inexpensive solution to the complex problem of ventilator-associated pneumonia (VAP). Although bacterial growth and colonization on these nanoetched materials have been well characterized, little is known about the mechanism by which the fungal lipase degrades the PVC and, thus, alters its properties to minimize bacteria functions. This study used X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Sheldon developed a new method for enzyme immobilization as CLEA (crosslinked enzyme aggregates). The method involves the precipitation of the enzyme from aqueous buffer followed by crosslinking with glutaraldehyde of the resulting physical aggregates of enzyme molecules [ 29 , 30 ]. CLEAs are shown to be stable, recyclable catalysts exhibiting high catalyst productivities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheldon developed a new method for enzyme immobilization as CLEA (crosslinked enzyme aggregates). The method involves the precipitation of the enzyme from aqueous buffer followed by crosslinking with glutaraldehyde of the resulting physical aggregates of enzyme molecules [ 29 , 30 ]. CLEAs are shown to be stable, recyclable catalysts exhibiting high catalyst productivities.…”
Section: Resultsmentioning
confidence: 99%
“…It could be explained by possible PVC degradation at these conditions and, consequently, releasing HCl into the medium. Very recently, lipase degradation of plasticized PVC has been studied [ 29 , 30 ]. It was reported that this degradation could yield HCl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the possibility to prevent VAP, other authors have demonstrated other procedures to prevent biofilm formation. Machado et al, have recently described a novel way of preventing biofilm formation on ETT surface by nanomodifying polyvinyl with a fungal lipase [ 38 , 39 ]. They also demonstrated that these modifications reduced P. aeruginosa colonization by 2.7 log 10 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, photolithographic etching of the Sharklet™ micro-pattern onto a silicone ETT surface resulted in a significant decrease in the accumulation of mucus inside the ETT, both in vitro and in vivo [ 21 ]. In addition, nanorough ETTs that can decrease bacterial growth and biofilm formation have also been introduced [ 22 ]; however, their widespread use is hindered by concerns over antibiotic resistance, coating stabilities, biocompatibility, and relatively high costs. Indeed, only silver-coated ETTs have been approved as antibiofilm ETTs in the USA, and to date, these coatings have been subjected to multiple clinical trials [ 14 ].…”
Section: Introductionmentioning
confidence: 99%